(15b-6)-7(2b+2)=-2

Simple and best practice solution for (15b-6)-7(2b+2)=-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (15b-6)-7(2b+2)=-2 equation:


Simplifying
(15b + -6) + -7(2b + 2) = -2

Reorder the terms:
(-6 + 15b) + -7(2b + 2) = -2

Remove parenthesis around (-6 + 15b)
-6 + 15b + -7(2b + 2) = -2

Reorder the terms:
-6 + 15b + -7(2 + 2b) = -2
-6 + 15b + (2 * -7 + 2b * -7) = -2
-6 + 15b + (-14 + -14b) = -2

Reorder the terms:
-6 + -14 + 15b + -14b = -2

Combine like terms: -6 + -14 = -20
-20 + 15b + -14b = -2

Combine like terms: 15b + -14b = 1b
-20 + 1b = -2

Solving
-20 + 1b = -2

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '20' to each side of the equation.
-20 + 20 + 1b = -2 + 20

Combine like terms: -20 + 20 = 0
0 + 1b = -2 + 20
1b = -2 + 20

Combine like terms: -2 + 20 = 18
1b = 18

Divide each side by '1'.
b = 18

Simplifying
b = 18

See similar equations:

| -13v+8-9v+12v= | | 19x-5(x-9x)+6x= | | 3y^2-16y=35 | | 8x+14x= | | 7d+10(1-6d)-4e= | | 7-x=-28 | | 3(n+5)=26 | | 17c+6(c-5c)-9c= | | X-7=28 | | -2(x-3)=x+5-3x | | 2x^2+2y^2=162 | | 15+8x-9(7x-3x)= | | 5.7q-2.8-4.9q=-0.2q-3.4 | | 8*30=12*x | | -4z+z-3(8z+6)= | | 13x+13=5x+5+7x | | -4(a+1)-3a=-7(2a-3) | | 21o-16p+3p+11p-9o= | | 16v^2+8v+1=0 | | 12+9a-6a+7a-15a+5a= | | 2x(x-3)=43 | | x^2-18x+50=0 | | 2x^2+6=8 | | -8y+6y-4y-13y= | | 4(3x+2)+2(5x-6)=5(2x+4) | | -4m+6=9m+31 | | -9b+6b-11b-3b= | | V^2-400=0 | | 10x+8-4+5x= | | 2(7x-3)+4=40 | | 14y+8=-5y+4 | | (-11a-8b)(-5a-6b)= |

Equations solver categories